Importation and early local transmission of COVID-19 in Brazil, 2020 - Jesus, Jaqueline Goes de (2020)
We conducted the genome sequencing and analysis of the first confirmed COVID-19 infections in Brazil. Rapid sequencing coupled with phylogenetic analyses in the context of travel history corroborate multiple independent importations from Italy and local spread during the initial stage of COVID-19 transmission in Brazil.